A review of functional magnetic resonance imaging studies with addictions of alcohol and drug - Çıkılı Uytun, Merve; Özdemir Demirci, Esra (Journal of Dependence, 2015)
Several current theories emphasize the role of functional brain abnormalities in addiction. In this review, the findings of the functional magnetic resonance imaging studies that examined neural deficits in addicted individuals are presented. We selected fMRI studies about tobacco, alcohol and drugs that using tasks such as stop-signal, go/no-go or resting state fMRI studies based on a search of PubMed and Google scholar. The findings showed that addicted individuals relative to healthy controls had abnormal activation patterns in the amygdala, insula, hippocampus, thalamus, striata, anterior cingulate cortex, inferior frontal gyrus, dorsolateral prefrontal cortex, temporal cortex, parietal cortex, and cerebellum. Although in some studies these neural deficits were associated with impaired task performance, other studies could not find such association. With regard to behavioral addictions, some evidence has been found for similar neural deficits; however, the data are limited and the results are not yet conclusive. This review focuses on functional neuroimaging studies conducted in the past decade that have expanded our understanding of the involvement of the several brain areas in addiction. Current addiction theories were supported by identifying consistent abnormalities in brain function in individuals with addiction.